Toniolo: un economista “keynesiano” e molto di più (Società e diritti, 2022)
The article considers some aspects of the complex socio-economic thought of Giuseppe Toniolo in the wake of some presentations of the book by Domenico Sorrentino, Bishop of Assisi (“Economia umana. La lezione e la profezia di Giuseppe Toniolo: una rilettura sistematica”, Vita e Pensiero, Milano, 2021). In particular, the figure of a "Keynesian well before Keynes" economist emerges on the need for policies to counter shocks, rich in wisdom on market and state failures, an advocate of an important role for intermediate bodies as well as a clear supporter of the impossibility to separate ethics and economics.